Solar Panel Monitoring and Control System Using Human Machine Interface - Azizah, Farah; Yuhendri, Muldi (LPPM Universitas Andalas, 2022)
The solar panel monitoring system based on the human machine interface is a system that can control and monitor the power generated by solar panels in the form of voltage, current, power, temperature, and solar radiation parameters in real time. PLC is used to monitor the panel work system in a long distance by utilizing PLC communication as an indicator of the reading status of the sensors used. As the interface between the PLC and the user, HMI is used. By using HMI visualization and technology a system can be made real. HMI is used to facilitate physical work and increase interaction between machines and operators through computer screen displays so that they can meet the information needed by users. The hardware used is a Programmable Logic Controller SIEMENS SIMATIC 1215C DC/DC/RL, Human Machine Interface SIMATIC KTP700 basic, ACS712, K type Thermocouple, and Pyranometer. Tia Portal software is used for programming and parameter setting of each system hardware.